Use of the Psychomotor Vigilance Test in Fitness for Work Assessments. Issue 8 (August 2017) - Lerman, Steven; Mollicone, Daniel; Coats, Sara
Abstract : Objective: The objective of the pilot program was to evaluate the utility of the psychomotor vigilance test (PVT) in aiding clinicians in making fitness for work determinations. Methods: A 10-minute PVT was incorporated into fitness for work examinations by occupational health staff at two integrated refining/petrochemical plants. Based on all evidence from the clinical examination, including PVT results, clinicians made their fitness for work determination. Results: Employees who were determined to be fit for work had significantly fewer PVT errors than did employees determined to be unfit for work or fit for work with limitations, with t (98) = −14.71, P < 0.001. Conclusions: The pilot assessed a new application of the PVT as an adjunct to occupational health evaluations focused on determining fitness for work. Results demonstrated that the PVT can be a valuable tool for this purpose.